(untitled) (Annals of Medical Research, 2022)
Aim: Although the length of hospital stay after lumbar microdiscectomy operations, one of the most common surgical interventions in current neurosurgery practice, is quite short, nausea-vomiting and urinary retention, particularly postoperative pain, may prolong this period. Also, systemic side effects may occur in cases due to pharmacological agents applied for postoperative pain control. This study was conducted to seek answers to whether bupivacaine administered intraoperatively into the paravertebral muscle mass decrease the need for postoperative narcotic analgesics and/or nonsteroidal anti-inflammatory drugs (NSAIDs). Materials and Methods: Lumbar disc hernia patients with a similar history of age, gender, body weight, disc hernia level, preoperative pain score, and preoperative analgesic use were included in the study between 01.06.2020 and 31.06.2021 (n=48). The control group of the study consisted of cases who did not receive paravertebral intramuscular bupivacaine during single-level lumbar microdiscectomy operations under general anesthesia and named as group 1 (n=24). The study group of the study consisted of cases who were administered preoperative paravertebral intramuscular bupivacaine and named group 2 (n=24). After the operation, the assessment of pain with the frequency of need for morphine sulfate or pethidine hydrochloride was performed with the Visual Analogue Scale (VAS). After the obtained data were assessed with a one-way analysis of variance, the relationship between parameters was tested using the Pearson correlation coefficient (r). Alpha significance value was accepted as <0.01. Results: It was found in comparisons between groups that the post-op VAS score (F=47.3; P=0.00), the post-op mobilization time (F=22.8; P=0.00), the post-op NSAIDs need (F=12.7; P=0.00), and the length of stay (F= 12.6; P=0.00) were statistically significant (P<0.01) in the groups using bupivacaine. However, in the cases in group 2, although the mean dose of post-op narcotic drug use decreased from 11.46±16.45 mg to 6.33±2.14 mg, it was reported that this result (F=0.5; P=0.47) was not statistically significant (P>0.01). It was determined that there was a moderate and positive relationship between the use of NSAIDs and the post-op VAS value and between the use of NSAIDs and post-op mobilization. It was determined that the post-op VAS score had a strong correlation above the moderate level with post-op mobilization time (r=0.609) and hospitalization time (r=0.603). Conclusion: In the cases for which pre-op paravertebral intramuscular bupivacaine was applied, although the decrease in the need for narcotic analgesics after the operation is not statistically significant, it was seen that it reduces the need for NSAIDS-featured dexketoprofen trometamol statistically and significantly. These results make us think that preoperative intramuscular bupivacaine administration may be effective in controlling postoperative pain and reducing the need for additional analgesics.